2022
DOI: 10.1108/bfj-07-2021-0752
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality and food safety systems adoption in the agri-food sector

Abstract: PurposeIn order to meet the increasingly demanding needs of international markets, quality and food safety systems have become widespread among companies in the agri-food sector. This has led to a transformation of the agri-food sector that has also been detrimental for companies seeking to adopt such standards. Therefore, the aim of this paper is to define the determining factors that affect the process of adopting quality and food safety standards in agri–food companies, from the implementation of standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Moreover, the poorest segment of small‐scale farmers has not experienced significant benefits from interventions by external donors. AccordinBarbancho‐Maya & López‐Toro (2022) identified that the high cost associated with implementing quality and food safety systems within organisations as the primary barrier to adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the poorest segment of small‐scale farmers has not experienced significant benefits from interventions by external donors. AccordinBarbancho‐Maya & López‐Toro (2022) identified that the high cost associated with implementing quality and food safety systems within organisations as the primary barrier to adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, their compliance with minimum food safety and quality standards poses a formidable obstacle to their integration into export markets. Governments impose minimum food safety standards to meet SDGs, satisfy the demands of high-end consumers and gain access to international markets (Do et al, 2019(Do et al, , 2022Barbancho-Maya & L opez-Toro, 2022;Yadav et al, 2023). Among food products, milk and milk products are the most perishable and need specialised handling and cold chain infrastructure at each stage of the milk supply chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic component can identify environmental chemicals or biological substances, as well as detect physiological changes, record them, and transmit the data. Biosensors are available in a variety of sizes and designs, and they can measure and detect even very low levels of certain diseases, harmful chemicals, and pH values (Barbancho-Maya & L opez-Toro, 2022). An analyte, a bio-receptor, a transducer, electronics, and a display make up a standard biosensor shown in Figure 1.…”
Section: Signal Detection and Analysismentioning
confidence: 99%
“…The establishment of an FSMS as required by the standard determines the application of a uniform approach on how to document the rules and define the scope of production in order to market safe food in harmonizing the requirements for commodities of plant origin nationally and internationally [32].…”
Section: Food Safety Management System According To the Requirements ...mentioning
confidence: 99%